2011
DOI: 10.1111/j.1530-9290.2011.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended Producer Responsibility in Thailand

Abstract: Summary Waste electrical and electronic equipment (WEEE) sheds light on the dimmer side of production and consumption patterns in modern societies. The rapid increase in its quantity and complexity contribute to the challenges it poses to solid waste management systems. Several members of the Organisation for Economic Co‐operation and Development (OECD) have relied on the principle of extended producer responsibility (EPR) to tackle the issue, with varying degrees of success. Several non‐OECD countries, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 20 publications
0
30
1
Order By: Relevance
“…One of the most common and popular policy instruments has been that of extended producer responsibility (EPR) (Khetriwal et al 2009;Manomaivibool and Vassanadumrongdee 2011;Özdemir, Denizel and Guide 2012). According to EPR, the responsibilities of companies extend till safe disposal of endof-lifecycle products.…”
Section: Discussion and Preliminary Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common and popular policy instruments has been that of extended producer responsibility (EPR) (Khetriwal et al 2009;Manomaivibool and Vassanadumrongdee 2011;Özdemir, Denizel and Guide 2012). According to EPR, the responsibilities of companies extend till safe disposal of endof-lifecycle products.…”
Section: Discussion and Preliminary Policy Implicationsmentioning
confidence: 99%
“…A number of small to medium scale organizations employing millions of people in many countries of the world, including women and children, are involved in managing e-waste generated domestically within a country as well as e-waste imported through largely illegal means (Manomaivibool and Vassanadumrongdee 2011;Manomaivibool 2009;Widmer et al 2005;Zoeteman, Krikke and Venselaar 2010). The largely informal nature of these organizations means that they are mostly outside the ambit of various national regulations on employment, trade practices, and environment.…”
Section: People-planet-profit and E-wastementioning
confidence: 99%
“…Prior research has identified the following as barriers to the implementation of nationwide WEEE management systems: presence of smugglers and informal importers, lack of commitment from governments, and a lack of recycling infrastructure and inappropriate policy instruments (Akenji et al 2011;Chi et al 2011;Chung and Zhang 2011;Hicks et al 2005;Kojima et al 2009;Manomaivibool 2009;Manomaivibool and Vassanadumrongdee 2011;Seitz and Wells 2006).…”
Section: Obstacles To the Participation In Product Take-backmentioning
confidence: 99%
“…The large majority of studies on the environmental effects of ICT have focused on energy‐related issues (Corcoran and Andrae ; Laitner ; Malmodin et al ; Masanet and Matthews ; OECD ). Materials‐related issues have only been discussed with regard to first‐order effects and have focused on three key areas of interest: Dematerialization (Weber et al ; Zapico et al ; Hogg and Jackson ) Material composition of ICT components and terminal equipment, such as personal computers (PCs) and cell phones (Andrae and Anderson ; Kuehr and Williams ; Williams et al ; Nissen et al ) Waste electrical and electronic equipment, recycling, and extended producer responsibility (Manomaivibool and Vassanadumrongdee ; Köhler et al ; Manhart ; Chancerel and Rotter ; Chancerel et al ; Schlepp et al 2009; Hilty ) …”
Section: Introductionmentioning
confidence: 99%
“…r Dematerialization (Weber et al 2010;Zapico et al 2010;Hogg and Jackson 2009) r Material composition of ICT components and terminal equipment, such as personal computers (PCs) and cell phones (Andrae and Anderson 2010;Kuehr and Williams 2003;Williams et al 2002;Nissen et al 2000) r Waste electrical and electronic equipment, recycling, and extended producer responsibility (Manomaivibool and Vassanadumrongdee 2011;Köhler et al 2011;Manhart 2011;Schlepp et al 2009;Hilty 2005) Studies on the environmental impacts of data centers have, to date, focused exclusively on energy-related issues (power use of servers, cooling, air conditioning, and so on) (EU CoC 2012; Koomey 2011;GFME 2008;Koomey 2008;US EPA 2007). Also, environmental guidelines (The Green Grid 2012; ASHRAE 2011), as well as auditing and certification schemes and environmental labels for data centers (ENERGY STAR 2012;EU CoC 2012;RAL GmbH 2011), have failed to address materials-efficiency issues.…”
Section: Introductionmentioning
confidence: 99%